Typenrevision der von Hellén beschriebenen Anomaloninae (Hymenoptera, Ichneumonidae) und Übersicht über die finnischen Arten - Schnee, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 2018)
The seven Anomaloninae species described by Hellen are revised. Valid species are Erigorgus romani (Hellen, 1926), Agrypon [nec Atrometoides] nigerrimum (Hellen, 1949), Barylypa helleni Schnee, 1989 [= Agrypon (Barylypa) rossicum Hellen, 1950 preoccupied by Barylypa rossicum Meyer, 1935], and Agrypon brachycerum Hellen, 1950. Habronyx scutellatus Hellen, 1926 is a syn. nov. of Agrypon flaveolatum (Gravenhorst, 1829), Anomalon boreale Hellen, 1926 of Erigorgus melanobatus (Gravenhorst, 1829) and Agrypon (Labrorychus) flaviventris Hellen, 1950 of Barylypa rubricator (Szepigeti, 1899). Erigorgus lapponicus (Thomson, 1892) is removed from synonymy with E. cerinops (Gravenhorst, 1829) and considered to be a good species. Two new species of the the Agrypon anxium group are described: Agrypon hinzi spec. nov. from Germany, Finland, Great Britain, Austria, Russia and Sweden and Agrypon capitatum spec. nov. from Finland. Aphanistes wadai Uchida, 1958 previously known only from the East Palaearctic is recorded for the first time from Finland and Germany. Aphanistes iwatai Uchida, 1958 is treated as a new synonym of A. wadai. A key to the West Palaearctic Aphanistes species is given. Faunistic and biological data with verified host records are provided. An updated checklist of the 44 Finnish Anomaloninae species is established. Nomenclatural Acts Agrypon hinzi spec. nov. – urn:lsid:zoobank.org:act:64B4346B-B89E-45D7-9C37-DD83F35D6CBA Agrypon capitatum spec. nov. – urn:lsid:zoobank.org:act:D73E4FDF-29F5-4BF3-BD6F-BB285387A125